Tooth segmentation by low-dose CBCT for orthodontic treatment planning: explorative ex vivo validation = Zahnsegmentierung anhand dosisreduzierter DVT für die kieferorthopädische Behandlungsplanung : explorative Ex-vivo-Validierung - Rütters, Maurice; Gehrig, Holger; Awounvo Awounvo, Junior Sinclair; Kim, Ti-Sun; Doll, Sara; Alexandrou, Korallia; Felten, Anna; Lux, Christopher J.; Sen, Sinan (Journal of orofacial orthopedics, 2026)
Three-dimensional imaging has become an increasingly important component of orthodontics. Associated with this, however, is a higher radiation exposure for patients. New cone-beam computed tomography (CBCT) devices have been developed that can provide low-dose CBCT (LD-CBCT). We hypothesized that LD-CBCT is as precise and reproducible as standard high-dose CBCT (HD-CBCT) in segmenting roots and crowns as well as measuring tooth length.